2016
DOI: 10.1002/prep.201500298
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Penetration of Jets by Shaped Charges with Reactive Material Liners

Abstract: 1IntroductionReactive material is ac lass of solid energetic materials with an adequate amount of strength and sufficienti nsensitivity [1].G enerally,t hey are formed by meanso fu niformly mixing active metal powders, alloyp owders or intermetallic compounds with ap olymer matrix (typically polytetrafluoroethylene) and consolidated via ap ressing process. These materials areformulatedtoself-initiate and release aconsiderable amount of energy under highly dynamic loads, thus efficient damage is achieved by inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 6 publications
(6 reference statements)
0
18
0
Order By: Relevance
“…Cu liner was sprayed with Al-Ni powder using a kinetic spray deposition method for enhanced reactive liner in [74]. Formation and penetration of jet composed of polymeric based reactive liner were studied numerically and observed by FXR in [75]. The liners were made by cold isostatic pressing at a pressure of 250MPa.…”
Section: Wwwetasrcom Naeem Et Al: a Review Of Shaped Charge Variables For Its Optimum Performancementioning
confidence: 99%
“…Cu liner was sprayed with Al-Ni powder using a kinetic spray deposition method for enhanced reactive liner in [74]. Formation and penetration of jet composed of polymeric based reactive liner were studied numerically and observed by FXR in [75]. The liners were made by cold isostatic pressing at a pressure of 250MPa.…”
Section: Wwwetasrcom Naeem Et Al: a Review Of Shaped Charge Variables For Its Optimum Performancementioning
confidence: 99%
“…The formability of active jets directly made of RSMs is generally poor due to the low density and poor strength of RSMs. These jets have much less penetration depth than traditional Cu jets although they have much stronger lateral effects on the targets [ 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [ 13 , 14 ] carried out a simulation test of PTFE-based energetic jet damage to a steel target, and studied the aftereffect overpressure characteristics of an energetic jet. In the aspect of jet forming, Wang et al [ 15 ] simulated the jet-forming process of a PTFE/Al liner by the Euler algorithm, and carried out an X-ray photography experiment. It was found that the diameter of the energetic jet was thicker, and the ductility was worse, than that of the metal jet.…”
Section: Introductionmentioning
confidence: 99%